2018
DOI: 10.31234/osf.io/kzbwf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of word meanings through metaphorical mapping: Systematicity over the past millennium.

Abstract: One way that languages are able to communicate a potentially infinite set of ideas through a finite lexicon is by compressing emerging meanings into words, such that over time, individual words come to express multiple, related senses of meaning. We propose that overarching communicative and cognitive pressures have created systematic directionality in how new metaphorical senses have developed from existing word senses over the history of English. Given a large set of pairs of semantic domains, we used comput… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Our proposal that more frequently colexified meanings should be more conceptually related is also consistent with recent evidence on how new word meanings enter lexicons over time (Ramiro et al, 2018;Xu et al, 2017). For example, Ramiro et al (2018) found that over the past 1,000 years, new meanings in English have much more often entered the lexicon by attaching to existing word forms than by creation of new forms.…”
Section: Figure 1 Illustration Of Colexification Across Languages Asupporting
confidence: 89%
See 1 more Smart Citation
“…Our proposal that more frequently colexified meanings should be more conceptually related is also consistent with recent evidence on how new word meanings enter lexicons over time (Ramiro et al, 2018;Xu et al, 2017). For example, Ramiro et al (2018) found that over the past 1,000 years, new meanings in English have much more often entered the lexicon by attaching to existing word forms than by creation of new forms.…”
Section: Figure 1 Illustration Of Colexification Across Languages Asupporting
confidence: 89%
“…Abstract concepts are often understood by reference to more concrete concepts (e.g., an argument as a war) (Lakoff & Johnson, 1980), and words that first arise with concrete senses often later gain an abstract one (Xu et al, 2017). We considered two versions of a metaphor-based model to take into account the possibility that colexification is driven by metaphorical tendency between concepts.…”
Section: And 5 Baselines Of Metaphoricitymentioning
confidence: 99%
“…Supporting this idea, studies on the developing Nicaraguan sign language have shown that complex linguistic structure emerges over multiple cohorts of learners (Senghas, Kita, & Ozyurek, 2004), and work on pidgins has suggested that new child learners are required in order to develop recursion (Bickerton, 1984). Second, it affects the reasoning and predictions made about the structure of human lexicons over time: from understanding trends in metaphorical mappings (Xu, Malt, & Srinivasan, 2017) to measuring the entropy and informativity of words (Bentz, Alikaniotis, Cysouw, & Ferrer-i-Cancho, 2017). Going beyond language evolution and change, this conclusion has already influenced work on a wide range of human behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…ref. 28). Our current work provides a starting point toward unlocking the algorithms that generate new word senses in lexical evolution.…”
mentioning
confidence: 99%